BIODIVERSITY OF ICHTHYOFAUNA IN THE DNIЕSTER DELTA - SERGII SNIGIROV (Revue Roumaine de Géographie)
The List of current Lower Dniеster fishes comprising 65 fish species belonging to 12 orders, 17 families and 52 genera is presented in the paper in a comparative approach. Analysis of the Lower Dniеster and the Dniеster Liman ichthyofauna structural characteristics has been carried out under conditions of regulated discharge, increasing pollution and spawning grounds degradation. Decrease in fish species composition has been shown, as well as the disappearance of some native reophilic and lithophilous fish species as the result of the Dniеster River discharge regulation. Data about rare species found in the Dniеster River and the Dniеster Liman are presented, including Benthophiloides brauneri Beling et Iljin, 1927, which has not been recorded in the Lower Dniеster before. The dwindling of catches of the main commercial fish species is also shown.